THE THEORETICAL INTEGRATIVE MODEL FOR THE LATVIAN CLINICAL PERSONALITY INVENTORY - Kolesnikova, Jelena; Perepjolkina, Viktorija; Martinsone, Kristine; Stepens, Ainars (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The purpose of this article is to present a theoretical integrative model, which reflects contemporary tendencies in the understanding of mental disorders and functional impairment, and which is used as a theoretical frame for the development of the Latvian Clinical Personality Inventory (LCPI). This article, based on the latest research findings in the field, supports the necessity of a combined analysis of mental disorders and functional impairment. Due to scientific findings and deeper understanding of the interrelation between mental disorders and functioning impairment, it has become possible to develop psychological instruments for valid assessment of the disturbances in an individual's cognition, emotion regulation, and behaviour combining with analysis of most essential and relevant aspects of their functioning. An integrative theoretical model of LCPI, developed on the selected criteria from Diagnostic and Statistical Manual of Mental Disorders (DSM – 5; APA, 2013) and WHO International Classification of Functioning, Disability and Health (ICF; WHO, 2001/2015) is presented in the article. Conducted literature analysis permits to conclude, that in a context of clinical personality assessment, a combined analysis of symptoms of mental disorders and relevant functioning criteria is very promising and will be useful in many assessment contexts. Based on such an integrative approach the Latvian Clinical Personality Inventory is currently being developed. This project is a part of the National Research Programme (No. 5.8.2.).